Becoming Steve Jobs : the evolution of a reckless upstart into a visionary leader - Schlender, Brent (Hodder&Stoughton Ltd., 2016)
"Based on the hugely popular cover story about Steve Jobs in Fast Company in May 2012, this is the behind the scenes account of how Steve Jobs arguably became the most famous and visionary CEO in history. Award-winning journalist Brent Schlender and veteran editor Rick Tetzeli have interviewed friends, industry insiders, and the people who knew Jobs best throughout his evolution as a CEO and leader. In addition Schlender, who knew Jobs personally for 25 years, has over 100 hours of interview tapes with Jobs to draw on, many hours of which have never before been transcribed"--